The art of blocking ADP-ribosyltransferases (ARTs): nanobodies as experimental and therapeutic tools to block mammalian and toxin ARTs - Menzel, Stephan (2013)
In 1901, the first Nobel Prize in Physiology or Medicine was awarded to Emil von Behring for his ground-breaking discovery of serum therapy: serum from horses vaccinated with toxin-containing culture medium of Corynebacterium diphtheriae contained life-saving 'antitoxins'. The molecular nature of the ADP-ribosylating toxin and the neutralizing antibodies were unraveled only 50 years later. Today, von Behring's antibody therapy is being refined with a new generation of recombinant antibodies and antibody fragments. Nanobodies, which are single-domain antibodies derived from the peculiar heavy-chain antibodies of llamas and other camelids, are emerging as a promising new class of highly specific enzyme inhibitors. In this review, we illustrate the potential of nanobodies as tools to block extracellular and intracellular ADP-ribosyltransferases (ARTs), using the toxin-related membrane-bound mammalian ecto-enzyme ARTC2 and the actin-ADP-ribosylating Salmonella virulence plasmid factor B toxin of Salmonella enterica as examples.